Innovation in Occupational Health And Safety Through Gamification to Improve Safety Compliance - Mohammad Abdul Kharim; Dewi Kurniasih; Priyambodo Nur Ardi Nugroho (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Occupational safety is a critical aspect in the construction sector, particularly in transmission network construction projects that involve high-risk activities such as working at heights and operating heavy equipment. Despite the implementation of established safety standards, work accidents remain a major concern, largely caused by unsafe actions performed by workers. This study aims to examine the effectiveness of gamification in improving safety compliance at PT Surveyor Indonesia, Surabaya Branch, specifically in transmission network construction projects. This research employs a quantitative approach with a descriptive correlational design. Data were collected using a Critical Behavior Checklist (CBC) to record unsafe actions and a questionnaire to measure workers’ perceptions of gamification elements. The testing of this application was conducted over a one-month period. The results indicate that the implementation of gamification was effective in significantly reducing the percentage of unsafe actions, which decreased from 69% before implementation to 24% after gamification was applied. The paired sample t-test results show a significance value (2-tailed) of 0.000, indicating a statistically significant difference between safety compliance levels before and after the implementation of gamification. Furthermore, the findings demonstrate that gamification elements such as point systems, rewards, and leaderboards enhance worker motivation and engagement in adhering to safety procedures, thereby reducing unsafe actions. This study contributes to occupational health and safety practices by providing empirical evidence that gamification can serve as an innovative and effective strategy to improve safety compliance in high-risk construction projects.